The contribution of fatty acids to the composition of the total lipids in juvenile Cape hake fillets - research - Swanepoel, H.; Lues, J.F.R.; Venter, P. (Journal for New Generation Sciences, 2016)
Due to the decline in fish stocks more juvenile fish are being caught. The aim of this study was to investigate the contribution of short and medium chain length fatty acids to the composition of the total lipids in juvenile Cape hake fillets and the impact thereof the nutritional value. The fatty acids that most contributed to the total fatty acid composition were palmitic acid (C16:0) (46.52%), docosahexaenoic acid (C22:6) (25.68%) and stearic acid (C18:0) (9.4%). Saturated fatty acid contribution to the total lipid content was found to be higher than reported in literature in other hake species and no eicosapentaenoic acid was detected. Eicosanoic acid, was detected only in the medium sized hake fillets, indicating reduced nutritional value in juvenile hake fillets. The challenges of the fishing industry is thus not only to control the sustainability of fish resources, but also the size of the total allowable catch to ensure the best nutritional level.
Published Article
Keywords: Fatty acids; Juvenile Cape hake; Nutrition